2018
DOI: 10.1111/joic.12527
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus aspiration in late presenters with ST‐elevation myocardial infarction: A single‐center randomized trial

Abstract: TA might be associated with improved reperfusion and myocardial salvage especially in STEMI patients presenting after 12 h from symptom onset who are likely to have a heavy thrombus burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…6 9 In late-acute MI, the thrombus may become organized over time, making predilatation and aspiration difficult in achieving antegrade flow. 10 11 12 As demonstrated in this case, these complications may be difficult to overcome with the conventional approach. Stenting of an atherothrombotic lesion with demarcated borders can reduce many complications during primary coronary intervention.…”
Section: Discussionmentioning
confidence: 89%
“…6 9 In late-acute MI, the thrombus may become organized over time, making predilatation and aspiration difficult in achieving antegrade flow. 10 11 12 As demonstrated in this case, these complications may be difficult to overcome with the conventional approach. Stenting of an atherothrombotic lesion with demarcated borders can reduce many complications during primary coronary intervention.…”
Section: Discussionmentioning
confidence: 89%
“…Ruben et al have reported that rheolytic thrombectomy was associated with a lower target vessel revascularization in patients with acute myocardial infarction complicated by cardiogenic shock 22 . Ahmed et al found that thrombus aspiration might be associated with improved reperfusion and myocardial salvage especially in STEMI patients presenting after 12 h from symptom onset 23 . Accordingly, further investigations on AngioJet rheolytic thrombectomy among patients with high risk is warranted.…”
Section: Discussionmentioning
confidence: 99%